INWERSJA TEMPERATURY POWIETRZA W TATRACH W LATACH 1995–2020 - GRAJEK, ZOFIA; SZYGA-PLUTA, KATARZYNA (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2021)
This paper concerns the characteristics of the multi-annual, seasonal and daily variability of thermal inversion in the Tatra Mountains in 1995–2020. The analysis was performed on the basis of hourly measurements taken at the Institute of Meteorology and Water Management National Research Institute (IMGW-PIB) station in Kasprowy Wierch and Zakopane. The types of atmosphere circulation were determined found when the inversion was most frequent. The concentration of PM10 during the inversion and its intensity were analyzed and indicated that the number of inversion cases was growing. The analysis confirmed that inversions were most frequent in the cold season in the evening hours during anticyclonic circulation. Strong inversions occurred in the cold season. Winter inversions were associated with an increase in PM10 concentration.